Synthesis and characterization of amorphous poly(ethylene oxide)/poly(trimethylene carbonate) polymer blend electrolytes - Rodrigues, Luísa (2012)
Solid Polymer Electrolytes (SPEs) have been proposed as substitutes for conventional non-aqueous electrolytes in various electrochemical devices. These promising materials may be of interest in various practical devices including batteries, sensors and electrochromic displays as they can offer high performance in terms of specific energy and specific power (batteries), safe operation, form flexibility in device arquitecture and low manufacturing costs. Many different host polymers have been characterized over the last 30 years, however a relatively un-explored strategy involves the use of interpenetrating blends incorporating two or more polymers. Electrolyte systems based on interpenetrating blends of known host polymers, poly(ethylene oxide) and poly(trimethylene carbonate), doped with lithium perchlorate, were prepared by co-dissolution in acetonitrile. This combination of polymer components results in the formation of a material that may be applicable in batteries and electrochromic devices. The results of characterization of polymer electrolyte systems based on interpenetrating blends of amorphous poly(ethylene oxide) and poly(trimethylene carbonate) host matrices, with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as guest salt, are described in this study. Electrolytes with compositions of n between 5 and 15 (where n represents the total number of cation-coordinating units per lithium ion) were obtained as flexible, transparent and free-standing films that were characterized by measurements of conductivity, cyclic voltammetry, differential scanning calorimetry and thermogravimetry.